INTERPRETASI PEREMPUAN KEPALA KELUARGA DI CYBER JOURNALISM BERDASARKAN SARA MILLS MODEL OF CRITICAL DISCOURSE ANALYSIS - Zuhri, Al; Susanti, Hera; Maulida, Desi; Nurdin, Hanifah; Miftahurrahmah (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
This research is elaborated with the intention of examining and critiquing whether cyber journalism today still exhibits a patriarchal attitude. Qualitative is a method applied by the Sara Mills Model of Critical Discourse Analysis as the basis for data analysis. The study results found that SindoNews.com is marginalized women-headed (widows) in their reporting. From January to March 2022, it was found that there were 60 news headlines about widows and 9 (nine) news headlines about widowers on the website. SindoNews.com reports in an unbalanced manner by disclosing the current percentage of widows but does not report the percentage of widowers in the same portion of news. In fact, when a divorce occurs, is not only the status of a widow, but also a widower. Then there are some news stories that discuss widowers and widows in the same portion of the news, but the titles that are highlighted are only widow status. SindowNews.com seems to prefer frying the word widow as the selling point of the news here. In addition, the status of widows was also found to be interpreted with negative tendencies, such as seductive names, thirst for sex life, women who should be pitied, perpetrators of crime, easy women, and other wild meanings. Based on the journalistic code of ethics, especially in articles (1) and (3), this kind of reporting is not feasible because the aspect of balance still needs to be fulfilled. However, the author does not deny that SindoNews.com also reports on widow cases with a positive tendency, although the intensity is small.